The effects of Acorus calamus L. in preventing memory loss, anxiety, and oxidative stress on lipopolysaccharide-induced neuroinflammation rat models - Esfandiari, Ebrahim; Ghanadian, Mustafa; Rashidi, Bahman; Mokhtarian, Amir; Vatankhah, Amir (International journal of preventive medicine, 2018)
Objective: Several factors lead to memory loss, the most important of which is brain aging that is caused mostly by neuroinflammation and oxidative stress. The need of finding preventive treatments of memory impairment in elderly encouraged authors to assess the effect of Acorus calamus on memory loss, anxiety, and antioxidant indices on neuroinflammation rat models. Materials and Methods: Different fractions of A. calamus were prepared. The subject rats were grouped in 11 groups of 10 each. In the nine treated groups, the extract gavage began 1 week before intraperitoneal (i.p.) injection of lipopolysaccharide (LPS) and continued for 2 weeks after the last injection of LPS. Behavioral tests, including passive avoidance and elevated plus-maze (EPM) tests, were run on days 24, 25, and 26 and the subjects were sacrificed on the day after the last behavioral test, and their hippocampus was isolated to measure the oxidative stress markers. Results: Assessment of oxidative stress markers in hippocampus samples revealed that the amounts of endogenous antioxidant enzymes (superoxide dismutase, glutathione peroxidase, and total antioxidant activity) in the groups that received different fractions were less than their equivalent figures in LPS-control group, and levels of malondialdehyde (MDA) in treatment groups were less than MDA level in LPS-control group. Moreover, the treatment groups with different fractions of A. calamus revealed better performance compared to LPS-control group in shuttle-box test. In EPM test, the groups with different fractions revealed lower stress level in comparison with LPS-control group. The best performance in memory test and the lowest level of stress in EPM was observed in the group with aqueous fraction at 600 mg/kg dose, and the least figures of oxidative stress markers were of the group with aqueous fraction at 600 mg/kg dose. Conclusion: The oral administration of different fractions of A. calamus, especially aqueous fraction, prevented from memory deficits and stress through controlling oxidative stress and inflammation processes.